Management Policy For Changes In The Semester Credit System (SKS) Superior Service Program in MAN 1 Medan and MAN 3 Medan: A Study Of Public Service Law - Asrul Nasution; Nurussakinah Daulay; Amiruddin Siahaan (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This study aims to analyze the change management policy in the Semester Credit System (SKS) flagship service program at MAN 1 Medan and MAN 3 Medan from the perspective of public service law. This study uses a multi-site study approach with locations at MAN 1 Medan, Jl. Willem Iskandar No. 7 B Medan, and MAN 3 Medan, Jl. Pertahanan, Kel. Timbang Deli, Medan Amplas District. Data collection techniques include observation, interviews, questionnaires, and documentation. Data analysis was carried out in two stages, namely, analysis in a single case and cross-case analysis. The results of the study indicate that change management planning at MAN 1 and MAN 3 Medan involved various parties, comprehensive plan adjustments, and gradual changes with improvements in facilities and human resources. The implementation of change management includes teacher and student collaboration, curriculum adjustments, and training and socialization. The evaluation at MAN 1 Medan focused on leadership, teachers, and curriculum revision, while at MAN 3 Medan, the evaluation emphasized the evaluation of technology facilities, socialization, and curriculum. From the perspective of public service law, MAN 1 and MAN 3 Medan have implemented legal principles in the implementation of education. This study provides insight into the effectiveness of change management policies in the SKS program and its implications for improving the quality of educational services in madrasas.